(3GdeMGSHI hGdGSJKeGQ hJMdjd GdbhGFe GdeGdjI QDjI GSJQGJjLjIs - (3ecQe YHO GdeSjM(B, (3HGSjdjs ((3GdbGgQI(B:s (3GdecJHI GdYUQjI GdefUhQI(B,s, 2007)
(3GdJYQja HGdHfhc(B:(3GdHfhc,GdHfhc GdJLGQjI,WHjY GdYedjGJ GdeUQajI(B:(3eUGOQ GdCehGd,ChLg GdGSJKeGQ,YQV GdfJGFL hGdQbGHI Ydi GdLgGR GdeUQaj(B:(3YQV fJGFL CYeGd GdHfhc,GdETQGa hGdQbGHI Ydi GdLgGR GdeUQaj,GdJMdjd GdeGdj ddbhGFe GdeGdjI aj GdHfcs
(3GdeQGLY U(B.279 ((3GbJfGAGJ (B2014 3(3f(B)s